Prinsip Kesantunan dalam Tuturan Akun Tiktok “Riezky.Kabah” - Falah Jauhari; Anindha Naila Shofa; Zuyyinatul Mushoffa; Achmad Fahman Alkahfi; Nanda Fatimatuz Zahro; Paramita Kusuma Wardani; Asep Purwo Yudi Utomo (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of digital technology, especially social media platforms such as TikTok, has had an impact that has driven changes in communication culture in society, one of which is related to the phenomenon of politeness crisis. This study aims to analyze the application of the principle of politeness in language in the speech used by the owner of the TikTok account